A method to study the hemodynamics of chicken embryo's aortic arches using optical coherence tomography. Issue 3 (4th November 2016) - Ko, Zhen Yu Gordon; Mehta, Kalpesh; Jamil, Muhammad; Yap, Choon Hwai; Chen, Nanguang
Abstract : Congenital cardiovascular defects are the leading cause of birth defect related death. It has been hypothesized that fluid mechanical forces of embryonic blood flow affect cardiovascular development and play a role in congenital malformations. Studies in small animal embryos can improve our understanding of congenital malformations and can lead to better treatment. We present a feasibility study in which high‐resolution optical coherence tomography (OCT) and computational fluid dynamics (CFD) are combined to provide quantitative analysis of the embryonic flow mechanics and the associated anatomy in a small animal model.